Emerging climate‐driven disturbance processes: widespread mortality associated with snow‐to‐rain transitions across 10° of latitude and half the range of a climate‐threatened conifer. (28th November 2016) - Buma, Brian; Hennon, Paul E.; Harrington, Constance A.; Popkin, Jamie R.; Krapek, John; Lamb, Melinda S.; Oakes, Lauren E.; Saunders, Sari; Zeglen, Stefan
Abstract: Climate change is causing rapid changes to forest disturbance regimes worldwide. While the consequences of climate change for existing disturbance processes, like fires, are relatively well studied, emerging drivers of disturbance such as snow loss and subsequent mortality are much less documented. As the climate warms, a transition from winter snow to rain in high latitudes will cause significant changes in environmental conditions such as soil temperatures, historically buffered by snow cover. The Pacific coast of North America is an excellent test case, as mean winter temperatures are currently at the snow–rain threshold and have been warming for approximately 100 years post‐Little Ice Age. Increased mortality in a widespread tree species in the region has been linked to warmer winters and snow loss. Here, we present the first high‐resolution range map of this climate‐sensitive species, Callitropsis nootkatensis (yellow‐cedar), and document the magnitude and location of observed mortality across Canada and the United States. Snow cover loss related mortality spans approximately 10° latitude (half the native range of the species) and 7% of the overall species range and appears linked to this snow–rain transition across its range. Mortality is commonly >70% of basal area in affected areas, and more common where mean winter temperatures is at or above the snow–rain threshold (>0 °C mean winter temperature). Approximately 50% of areas with a currently suitable climate for the species (<−2 °C) are expected to warm beyond that threshold by the late 21st century. Regardless of climate change scenario, little of the range which is expected to remain suitable in the future (e.g., a climatic refugia) is in currently protected landscapes (<1–9%). These results are the first documentation of this type of emerging climate disturbance and highlight the difficulties of anticipating novel disturbance processes when planning for conservation and management.